2021
DOI: 10.3389/fphys.2021.755598
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 Regulates Goat Intramuscular Adipogenesis Through Focal Adhesion Pathway

Abstract: Intramuscular fat (IMF) deposition is one of the most important factors to affect meat quality in livestock and induce insulin resistance and adverse metabolic phenotypes for humans. However, the key regulators involved in this process remain largely unknown. Although liver kinase B1 (LKB1) was reported to participate in the development of skeletal muscles and classical adipose tissues. Due to the specific autonomic location of intramuscular adipocytes, deposited between or within muscle bundles, the exact rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…We will explore the molecular mechanisms of these genes in the future. Meanwhile, we found that DEMs, DECs and DELs were significantly enriched in the Focal adhesion and the ECM-receptor-interaction pathways, which was consistent with the findings in goat and chicken IMF [ 42 , 43 ]. Studies have found that focal adhesion kinase (FAK) and ECM-receptor interactions can regulate intramuscular adipogenesis in goats and chickens [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 87%
“…We will explore the molecular mechanisms of these genes in the future. Meanwhile, we found that DEMs, DECs and DELs were significantly enriched in the Focal adhesion and the ECM-receptor-interaction pathways, which was consistent with the findings in goat and chicken IMF [ 42 , 43 ]. Studies have found that focal adhesion kinase (FAK) and ECM-receptor interactions can regulate intramuscular adipogenesis in goats and chickens [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 87%
“…Studies have shown that the FAK participated in adipocyte differentiation, and its cleavage by calpain was required to fulfill the final maturation of adipocytes [ 25 ]. Study had also shown that liver kinase B1 (LKB1) inhibited goat intramuscular adipogenesis through the FAK pathway, blocking this pathway rescued the observed phenotypes in LKB1 knockdown adipocytes [ 26 ]. MAPK phosphatase-1 (MKP-1) plays an essential role in adipocyte differentiation through down-regulation of p42/p44 MAPK activity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two circRNAs, circ_0005870 and circ_0000946, were found existed in both focal adhesion [ 24 , 25 ] and PI3K-Akt signaling pathways [ 11 , 26 ] in this study, which given a great possibility of their functions in adipocyte differentiation. Therefore, we further performed prediction analysis to find the potential target genes of miRNAs that interacting with these two circRNAs.…”
Section: Resultsmentioning
confidence: 85%